The Effectiveness of Oxytocin Massage with Breast Care Against Breast Milk Production in Post Sc Mothers - Yakomina Mahulette; Mundarti Mundarti; Masini Masini (Poltekkes Kemenkes Semarang, 2022)
Background: Conditions that affect milk production include the use of medications such as ideas that are used during surgery. Postoperative pain affects the mother to delay breastfeeding and interferes with the lactation reflex, so the mother needs time to recover. Breast milk production affecting by two hormones: the hormone prolactin and the hormone oxytocin. A message from the mother's spine can stimulate the hormone oxytocin. This study aims to clarify the effectiveness of oxytocin and breast care massage on maternal milk production after SC. Methods This type of quasi-experimental study is only a post-experimental design with a control design. The population of this study were mothers who had SC during March and May 2021. 44 respondents were selected based on random sampling. This study was divided into two groups. Intervention group: mothers after SC received oxytocin massage while control. Results: The results showed that the average weight gain of babies on day 3 of the oxytocin massage group was 85 grams and 256 grams on day 7 of the massage. While the mean weight gain of children on day 3 in the Maternal Care group was 52 grams, and on day 7, the mean weight gain of children was 155 grams. Based on bivariate test results shows that oxytocin massage has more effect significantly in breast milk production of post-SC mothers (p-value: 0.000). Conclusion Therefore, in the case of mothers after SC Willing to receive oxytocin massage treatment to promote milk production.